2014
DOI: 10.2169/internalmedicine.53.2344
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Retrospective Survey of Poisoning after Consumption of Products Containing Synthetic Chemicals in Japan

Abstract: Objective We conducted a multicenter retrospective survey of patients poisoned by synthetic chemicals (SCs) in Japan. Methods Letters were sent to 467 emergency facilities requesting participation in the study, and questionnaires were mailed to facilities that agreed to participate. Patients The study participants were patients who were transported to emergency facilities between January 2006 and December 2012 after consuming SC-containing products. Results We surveyed 518 patients from 60 (12.8%) facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
0
31
0
2
Order By: Relevance
“…Nevertheless, this similarity does not mean C and SCs have similar risks, regarding that clinical cases with serious adverse effects and deaths related with SCs reported in the literature. 4,5,9,10,12,18 The relative risk associated with the use of SCs was found to be 30 times higher than that associated with C; and significantly more symptoms were reported by respondents seeking treatment for SCs than for C. 10 Although both Δ-tetrahydrocannabinol and SCs stimulate the same receptors (CB1 and CB2); studies have shown that SCs are associated with higher rates of toxicity and hospital admissions than natural C. 6 This is likely due to SCs being direct agonists of the cannabinoid receptors, whereas C is a partial agonist. Furthermore, the different chemical structures of SCs may interact in unpredictable ways to elicit previously unknown effects, also the commercial products may have unknown contaminants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this similarity does not mean C and SCs have similar risks, regarding that clinical cases with serious adverse effects and deaths related with SCs reported in the literature. 4,5,9,10,12,18 The relative risk associated with the use of SCs was found to be 30 times higher than that associated with C; and significantly more symptoms were reported by respondents seeking treatment for SCs than for C. 10 Although both Δ-tetrahydrocannabinol and SCs stimulate the same receptors (CB1 and CB2); studies have shown that SCs are associated with higher rates of toxicity and hospital admissions than natural C. 6 This is likely due to SCs being direct agonists of the cannabinoid receptors, whereas C is a partial agonist. Furthermore, the different chemical structures of SCs may interact in unpredictable ways to elicit previously unknown effects, also the commercial products may have unknown contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…3,7 SCs have full agonistic effect on both central nervous system cannabinoid type 1 (CB1) and type 2 (CB2) receptors, whereas C is a partial agonist of these receptors. 5,8 As a result, SCs potentially pose a greater risk to users' health than natural forms of C. 9,10 Abuse of SCs has been shown to produce serious adverse health effects, including but not limited to hyperactive delirium, psychotic episodes, acute kidney injury, seizures, stroke, myocardial infarctions, and even occasional deaths. 5,11,12 In addition to adverse effects, withdrawal symptoms such as agitation, irritability, anxiety, mood swings, nausea, loss of appetite, sweating and headache were reported by SC abusers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, dramatic increase have been seen in intoxication cases due to use of SC in Japan in the last few years. As well as physical complications, behavioral pathologies and psychotic symptoms were also observed in these cases (5). In US National Poison Data System records of 2015, serious side effects has been found in 11.3% of the acute intoxication cases due to SC use (4).…”
Section: Introductionmentioning
confidence: 94%
“…While it was found that users in Europe and the US are mostly adolescent and young adult males (1,6), SC using age in Japan was reported to be higher when compared to Western countries (5). It was found in studies that the use of other psychoactive substances with SC is common and the most commonly used psycho-active agents are alcohol and cannabis (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation